Influence Study Of Self-Management and Nursing Services Quality During Covid-19 Pandemi At The Bethesda Lempuyangwangi Hospital Yogyakarta - Damas Krismantaka Aji; Vivi Retno Intening; I Wayan Sudarta; Yullya Permina (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Background: The quality of nursing services is the most important part of creating health services in a hospital. Self-management is one way to be able to change behaviors, thoughts, and feelings. Nurse mentioned that the quality of service had decreased due to the uncomfortable workspace and working atmosphere during Covid-19 Pandemic. Objective: This research aimed to find the effect of self-management on nursing services quality at Bethesda Lempuyangwangi Hospital Yogyakarta. Method: This consisted pre-experimental research design with one-group pre and post-test model. The population was nurses at Bethesda Lempuyangwangi Hospital. The sample obtained was 38 nurses taken with purposive sampling technique. This study used a questionnaire on the quality of nursing services and provided intervention on self-management through online meeting. Data analysis was proceed applying Wilcoxon sign rank test with 95% confidence level. Result: The P-value was 0.074 (p>0.05). The pre-test result showed 23 nurses who were very good (60.5%) and the post-test showed 30 nurses who were very good (78.9%). Conclusion: There is no effect of self-management on the quality of nursing services during the Covid-19 pandemic at Bethesda Lempuyangwangi Hospital Yogyakarta.